Comparative Analysis of the Antimicrobial Efficacy of Selected Medicinal Plant Extracts and Conventional Antibiotics against Pathogenic Bacteria - Kadhim, Mohammed J. (American Journal of Bioscience and Clinical Integrity, 2025)
Increased prevalence of antimicrobial-resistant microorganisms has prompted the quest globally for new antimicrobial agents, particularly from nature. In this study, an effort is made to compare and evaluate the antimicrobial activity of certain selected medicinal plant extracts—Azadirachta indica (neem), Ocimum sanctum (tulsi), and Curcuma longa (turmeric)—with reference antibiotics against some common pathogenic bacteria like Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. The plant extracts were also obtained through both aqueous and ethanol-based extraction processes and tested for antimicrobial activity through the disc diffusion assay. Antibiotics ampicillin and ciprofloxacin were employed as control. The MIC and MBC of each extract were also ascertained. Initial results indicate that ethanol extracts contain greater inhibition zones than aqueous extracts, where Ocimum sanctum exhibited the highest antimicrobial activity. While the conventional antibiotics were generally more active, certain plant extracts had synergistic or similar effects, particularly against Gram-positive bacteria. The results suggest that some bioactive compounds from plants possess significant antimicrobial activity and could serve as complementing or supplementary therapies to conventional antibiotics. The study affirms the potential of ethnobotanical materials in the fight against the increasing menace of antimicrobial resistance.